Communicative-Pragmatic Treatment in Schizophrenia: A Pilot Study - Bosco, Francesca M.; Gabbatore, Ilaria; Gastaldo, Luigi; Sacco, Katiuscia (Frontiers in Psychology, 2016)
This paper aims to verify in patients with schizophrenia, the efficacy of Cognitive Pragmatic Treatment (CPT), a new remediation program for improving communicative-pragmatic abilities. The CPT program consists of 20 group sessions, focused on several communication modalities, i.e. linguistic, extralinguistic and paralinguistic, Theory of Mind (ToM) and other cognitive functions that can affect communicative performance, such as awareness and planning. A group of 17 patients with schizophrenia participated in the training. They were tested before and after training, using the equivalent forms of the Assessment Battery for Communication (ABaCo), a tool for evaluating the comprehension and production of a wide range of pragmatic phenomena such as, i.e. direct and indirect speech acts, irony and deceit, and a series of neuropsychological and ToM tests. The results showed a significant improvement in patients’ performance following the program, on both comprehension and production tasks, and in all the communication modalities assessed by the ABaCo, i.e. linguistic, extralinguistic, paralinguistic and social appropriateness. The improvement of patients’ performance persisted after three months from the end of the training, as shown by the follow-up tests. These preliminary findings support the efficacy of the CPT program in improving communicative-pragmatic abilities in the patients.